AB0302 Influence of Tapering Biological Therapies in Immunogenicity in A Cohort of Rheumatoid Arthritis with Low Disease Activity. (15th July 2016) - Paredes, B.; Plasencia, C.; Balsa, A.; Monjo, I.; Plasencia, C.; Pascual-Salcedo, D.; Monjo, I.; Pieren, A.; Moral, E.; Tornero, C.; Bogas, P.; Bonilla, G.; et al.
Abstract : Background: Recent studies propose the use of a tapering strategy (dose reduction or discontinuation) of tumor necrosis factor inhibitors (TNFi) in rheumatoid arthritis (RA) patients (pts) in low disease activity (LDA) or clinical remission (R) without losing the disease control. One concern, when lower doses are used, is the appearance of anti-drug antibodies (ADA) with the consequent loss of efficacy. Objectives: To evaluate the clinical influence of the tapering strategy of TNFi in a cohort of RA pts in LDA or R. Methods: Of a total of 283 RA pts under TNFi, 52 patients treated with Infliximab (Ifx), Adalimumab (Ada) or Etanercept (Etn) were selected. All pts were in LDA or R (DAS28 <3.2 or <2.6, respectively) for at least 6 months prior to start the tapering strategy. Clinical activity (DAS28), drug levels (DL) and ADA were evaluated at baseline before tapering (pre-visit) and at the last available visit after 4 years follow-up (final-visit), this parameters were also evaluated at flares (DAS28>3, 2 and ΔDAS28>0.6). At flare, the biologic and non-biologic therapy could be intensified. Results: In our cohort of 52 pts, 26 (50%) pts were treated with Ada, 16 (31%) with Etn and 10 (19%) with Ifx. Forty one (79%) were women and 41 (79%) pts were ACPA+ and RF+. Most patients received methotrexate concomitantly (69%), 25 (48%) pts other DMARDs and 22 (42%) prednisone. The mean follow-up was 43.76±8months, without statistically significance among TNFi (p=0.595). At pre-visit, 40 (77%) pts were in R and 12 (33%) LDA. The majority of patients remained in LDA or R at final-visit: 26 (50%) in R, 14 (27%) in LDA, 12 (23%) with DAS28>3.2, p=0.97). When a subanalysis in each TNFi was performed, it was confirmed that most pts were in LDA or R at final-visit (p=0.59 in Ada, p=0.26 in Ifx and p=0.78 in Etn). No differences in CRP levels between visit-pre and final visit were seen. 25 patients (48%) had flares during follow-up (13 (52%) had 1 flare, 10 (40%) had 2 flares and 2 (8%) had 3 flares. Most patients with flares were in LDA or R at final-visit (R=9 (36%), LDA=5 (20%)). Only 2 pts with flares dropped out the TNFi and were ADA + at final visit. All patients were ADA negative at the pre-visit and only 6 (11%) were positive at final-visit, 4 of them withdrawed therapy for maintaining clinical remission. A statistically significant decrease was observed in drug levels between the pre-visit and post-visit (Ada: 5251.9±1205.9 vs 1507.2±322.7, p=0.001; Etn: 2735.2±347.4 vs 1114.9±283.2, p=0.002; Ifx: 2358.4±728.5 vs 650.4±290.1, p=0.008). Conclusions: The tapering strategy seems feasible in RA pts in LDA treated with TNFi, reducing the amount of drug administered with low incidence of ADA and without deterioration of disease activity. In most patients, flares appear to be controlled by changing the drug administration interval without the necessity of changing or stopping treatment. Disclosure of Interest: B. Paredes Grant/research support from: This work was funded by an unrestricted research grant from Pfizer, C. Plasencia: None declared, A. Balsa: None declared, I. Monjo: None declared